Virulence of fowl adenovirus (FAdV) serotype 4 strains impacts cell proliferation and immune response of primary chicken-embryo intestinal epithelial cells - Katharina Kau-Strebinger; Ursula Reichart; Taniya Mitra; Beatrice Grafl; Michael Hess; Dieter Liebhart (Veterinary Research)
Abstract Fowl adenovirus serotype 4 (FAdV-4) causes hepatitis-hydropericardium syndrome (HHS) in chickens, leading to substantial economic losses. Following oral uptake, the virus infects intestinal epithelial cells (IEC) to overcome the first entrance barrier. The initial cellular interactions and intestinal immune responses are not well understood. This study uses a primary IEC culture model to investigate infection dynamics of virulent (AG234) and non-pathogenic (KR5) FAdV-4 strains and cellular defence mechanisms. Cell growth and viral propagation were assessed at 4, 12, 24, and 48 hours post-infection (hpi) using immunofluorescence and automated image analysis. The innate immune response was assessed by the mRNA expression of the Toll-like receptors (TLR1B, TLR2B, TLR3, TLR4, and TLR21) and the cytokines (IL-1β, IL-6, IL-10, IL-13, and IFN-γ). KR5 did not significantly reduce IEC growth; notable proliferation between 4 and 48 hpi was observed. Although IEC growth was initially similar, AG234 decreased cell numbers at 48 hpi. Compared to KR5, the abundance of AG234-infected cells was already higher at 4 hpi. Nevertheless, at 48 hpi, the number of IEC infected with the virulent strain was less than KR5, albeit without significance. The AG234 infection primarily activated the immune response at 48 hpi, characterised by a significant mRNA up-regulation of TLR3, TLR21, IL-1β and INF-γ compared to the negative control. KR5 induced a substantially higher expression of IL-13 mRNA compared to the control at 48 hpi. The results show that FAdV virulence significantly affects cell growth, viral augmentation, and the immune response. The chicken IEC culture system presented in this study effectively propagates FAdVs to examine the initial stage of intestinal infection.